THE EFFECT OF COOPERATIVE LEARNING MODELS TYPE GROUP INVESTIGATION AND KINESTHETIC STYLE LEARNING TO SCIENCE PHYSICS SKILL PROCESS ON STUDENTS - Sriutami Kholila Mora Siregar; Nurdin Bukit (Universitas Negeri Medan, 2014)
The purposes of the research are: to determine differences in the physics skills of students with learning model Cooperative Group Investigation using concept maps and Direct Instruction teaching model, to determine differences in the physical skills of students who have high Kinesthetic Learning Styles and Learning Styles low, to determine the interaction between Models of Learning and Kinesthetic Learning Styles toward physical process skills of students. The sample in this study conducted in a cluster random sampling of two classes, where the first class as a class experiment applied learning models Cooperative Group Investigation using Concept Maps as a class and the second class of controls implemented Direct Instruction model. The instrument used in this study is physics instrument science process skills in narrative form as many as 13 questions and instrument kinesthetic learning style questionnaire that has been declared valid and reliable. The results were found: there are differences in physical science process skills students are taught by Cooperative Group Investigation learning model using Concept Maps and Direct Instruction teaching model. There are differences in physical science process skills of students who have kinesthetic learning styles and students who have low kinesthetic learning style. Interaction between learning models Cooperative Group Investigation using Concept Maps and kinesthetic learning styles in influencing the physical science process skills of students.